Improvement of lipid productivity on chlorella vulgaris using waste glycerol and sodium acetate - Estévez-Landazábal, Laura-Lucía; Barajas-Solano, Andrés-Fernando; Barajas-Ferreira, Crisóstomo; Kafarov, Viatcheslav (CT&F - Ciencia, Tecnología y Futuro, 2013)
Although microalgae have great potential as a raw material for biodiesel production it is necessary to increase both biomass and lipids productivity. One way to achieve this goal is the implementation of mixotrophic cultures and the regulation of carbon/nitrogen ratio. The present work aims to improve the productivity of biomass and lipids in Chlorella vulgaris UTEX 1803 using waste glycerol from biodiesel production (1, 5 and 10% v/v) and sodium acetate (5, 10 and 20 mM) as carbon sources together with modification of the initial concentration of nitrogen (1.02; 1.47 and 2.94mM de NaNO3). All experiments were performed at 23±1ºC, with light: dark cycles of 12:12 h during 5 days. In biomass production was achieved a significant increase (80% higher that autothrophic cultures without modification). The best percentages of lipids exceeded control culture up to 2.18. Lipid productivities were also found 2.83 and 3.5 times greater than control. Results show the possibility of increasing the production of biomass and lipids by applying the carbon/nitrogen ratio using as a carbon source waste glycerol of the biodiesel industry that opens up great possibilities for the re-use of this residue thus increasing the sustainability of the process in general, Also has been proved that carbon/nitrogen ratio using sodium acetate is an interesting alternative due to his low cost carbon/nitrogen ratio using sodium acetate is an interesting alternative.